Human life cycle and the beginning of life : an Islamic perspective - Abd-El-Maeboud, Karim Hassanein Ismail (Array, 2009)
Although the definition of the beginning of life is rather difficult, Islamic teachings clarify that ensoulment – occurring after 40 or 120 days from conception – is a crucial point. However, Islam confers respect and protection earlier to this point. Considering basic human rights as decreed in Islam, there is an escalation in gaining these rights from fertilization up to delivery. Although this escalation clarifies the absence of full human rights of a developing fetus till being viable and born alive, it does not negate one basic right, »the right to life«, i.e. to be protected as a potential human being with eventual full human rights. As shown here, the close matching between Qur'an, the word of Allah, and science, the deeds of Allah, poses no major conflicts in defining the start of human life. The consensus is that from the moment a zygote is formed, it deserves a unanimously recognized degree of respect. The occurrence of ensoulment after 40 days should not be taken as a prelude to justify unaccepted tampering with on a man-to-be developing zygote